The fluorometric response of cyanobateria to short exposure of heavy metal - Wong, Ling Shing; Lee, Yook Heng; Surif, Salmijah (AENSI Publications, 2012)
This study is focused on the response of cyanobacteria Anabaena torulosa to a short exposure to copper. Measurement was based on the differential of the fluorescence signal of the organism before and after the exposure to copper, with excitation and emission set at 526 nm and 648 nm respectively. To optimize the yield of fluorescence signal, the day-7 culture of cell suspension was used with the density of OD700nm= 0.45 A, with short exposure time of 8 minutes to Cu. Tests on different concentration of Cu showed the cyanobacteria fluorescence yields formed a linear range from 1 – 10 μg/L. The cyanobacteria could be a good candidate for biosensor for producing signals under a short exposure to low concentration of Cu.